2002
DOI: 10.1007/s00330-002-1353-y
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injuries: role of imaging in the management of the polytrauma victim (conservative expectation)

Abstract: Abdominal US and CT play an important role in the initial management of blunt trauma in adults. Ultrasound is an excellent method for detection of free intra-abdominal fluid. It is the modality of choice for initial screening and enables selection of hemodynamically unstable trauma victims with severe hemoperitoneum for immediate surgery. However, even in experienced hands, US is not sufficient to rule out organ injuries reliably. Computed tomography, and particularly multislice CT (MSCT), has several major ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 51 publications
(75 reference statements)
0
68
0
6
Order By: Relevance
“…Although a well-known phenomenon in clinical medicine, the pattern and extent of missed injuries vary depending on the setting and the time period under study (7, 18 -24). It is likely that the proportion of missed injuries has decreased over time, as a result of implementation of structured clinical assessment of trauma victims (25) and improved diagnostic procedures (26). Nevertheless, in a study on traumarelated deaths in an intensive care unit by Ong et al (14), new major diagnoses were found in 19% of the autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a well-known phenomenon in clinical medicine, the pattern and extent of missed injuries vary depending on the setting and the time period under study (7, 18 -24). It is likely that the proportion of missed injuries has decreased over time, as a result of implementation of structured clinical assessment of trauma victims (25) and improved diagnostic procedures (26). Nevertheless, in a study on traumarelated deaths in an intensive care unit by Ong et al (14), new major diagnoses were found in 19% of the autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Unsere eigenen Erfahrungen an mehr als 500 Patienten bestätigen diese Annahme, da die diagnostische Sicherheit durch den Einsatz der MSCT erhöht wird und der Zeitaufwand für die diagnostische Abklärung erheblich verkürzt werden kann. Diese Einschätzung wird auch von anderen Autoren geteilt, wie jüngste Literaturberichte zeigen [7,26,39]. …”
Section: Schlussfolgerungunclassified
“…Furthermore, these injuries lead to a higher mortality in the multiple injured patients than isolated injuries of the same region [5]. In trauma patients, a clear history is rarely available as most patients are confused, unconscious or even anesthetized and the clinical findings have been shown to be equivocal or misleading in 20-50% of victims of blunt poly-trauma [6]. With the wide availability of Spiral computed tomography (CT) scanner overuse and perhaps overdependence on CT results for the management of patients with chest trauma has occurred.…”
Section: Introductionmentioning
confidence: 99%